Derivados oleananos e ursanos e sua importância na descoberta de novos fármacos com atividade antitumoral, anti-inflamatória e antioxidante - Dalla Vechia, Luciana (2009)
Oleanolic and ursolic acids are triterpenes that exist abundantly in the plant kingdom. They show antitumor activity and their cytotoxic activity was already evaluated against a broad range of cell lines. The inhibition of enzymes involved in the metabolism of DNA and the induction of apoptosis are known events that have been related to the antitumour activity of these triterpenes. The antiinflamatory and antioxidant activities also seem to play an important role in their antitumour activity. In this review, it is presented an overview of the importance of the potential antitumour, antiinflamatory and antioxidant activities of these triterpenoid derivatives. Also, we propose a structural-activity relationship to triterpenes containing oleanane or ursane skeleton and their cytotoxic activity.